LIQUID CRYSTAL DISPLAY DEVICE - YAMADA YUMIKO (1996)
PURPOSE: To provide a high contrast with good display property without causing white or black collapse by making gradient voltage with lowest gradient data output from a gradient data signal control means larger than voltage where the light transmissivity of a liquid crystal layer begins to chage, when a gradation is displayed by using a FRC drive method. CONSTITUTION: A scanning electrode drive means 2 and a scanning electrode drive means control circuit 6 to output a gate voltage to a scanning electrode, a signal electrode drive means 4 and a signal electrode drive means control circuit 7 to output a N-bit gradation of gradient voltage on a signal electrode and a gradient data signal control means driven by an opposite electrode drive means 5 and an opposite electrode drive means control circuit 8 to output gradient data 12 to a signal electrode drive means 3 are provided. The dradient voltage for lowest gradient data 12 output from a gradient data signal control means 9 is made larger than voltage (Vc) where the light transmissivity of a liquid crystal layer begins to change.